A polarisable QM/MM description of NMR chemical shifts of a photoreceptor protein. (17th October 2020) - Hashem, Shaima; Cupellini, Lorenzo; Lipparini, Filippo; Mennucci, Benedetta
ABSTRACT: We present a polarisable QM/MM investigation of NMR chemical shifts of a photoreceptor protein belonging to the Blue Light-Using Flavin family. Two different structures have been proposed for this photoreceptor which show a large variability in terms of the position and orientation of the protein residues around the flavin chromophore. Here, the two structures have been investigated with our multiscale approach using both DFT and MP2 level of theory. The picture that comes out comparing the 1 H chemical shifts of the flavin and the most strongly interacting protein residues with the available experimental data, indicates a different behaviour of the two structures, with one showing a better correlation with NMR measurements. This shows that hybrid quantum chemical-classical simulations of NMR chemical shifts can indeed become a valuable tool to investigate the structure of complex biosystems. GRAPHICAL ABSTRACT: